Advances in Mathematical Modeling and Experimental Methods for Materials and Structures The Jacob Aboudi Volume - Gilat, Rivka; Banks-Sills, Leslie (Solid Mechanics and Its Applications,, 2009)
This work presents a collection of papers, written by leading authors in honor of Professor Jacob Aboudi. Jacob Aboudi served as Head of the Department of Solid Mechanics, Materials and Structures, as Dean of the Faculty of Engineering and as Incumbent of the Diane and Arthur Belfer Chair of Mechanics and Biomechanics at Tel Aviv University. Aboudi has published more than 200 papers, 2 books and is a leading authority in the field of composite materials. The papers in this volume cover a wide spectrum of topics in the forefront of research in experimental methods and mathematical modeling of materials and structures. Subjects treated include developments in materials science, theoretical and applied mechanics, applied mathematics, applied physics, computational methods in engineering, mechanical and civil engineering. Both theoretical and experimental approaches are presented. As this book reflects the state of the art, possible engineering applications and future research directions are suggested.